تقنيات السرد في رواية أسعد اللامي (اونسام كاميل) - , Dr. Raad Hoyer Swailem (Thi Qar Arts Journal, 2021)
The narrative structure, with its multiple techniques, is an essential component of the narrative text, which makes the narrative work open to the sounds of life as a whole. It has to be that the narration process is a functional process in building that narrative, and it is good to facilitate its entrances to be effective and influential. The novel, as a literary genre, remains in a state of permanent formation and continuous becoming; Because it derives its existence and entity from a society and a historical circumstance that is full of life and does not know silence. Because the novel is dependent on the reality that produces it, its horizon expands with its richness, and its buildings are renewed, which will overflow on literature through it, giving it a special form, thus forming the multiple narrative forms with their different formulations, which are the result of this lively movement in the veins of that society that embraces it.